THE EFFECT OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND EDUCATION LEVEL ON FINANCIAL MANAGEMENT BEHAVIOR OF MSMES ACTORS IN TEJAKULA DISTRICT - Putra, I Gede Ariesta Prasetya Dinata Adnyana; Masdiantini, Putu Riesty; Devi, Sunitha (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Financial management behavior is an important concept in financial science because it helps business actors in managing and utilizing their business financial resources. This study is a quantitative study with an associative approach with the aim of determining the effect of financial knowledge, financial attitudes, and education levels on the financial management behavior of MSME actors in Tejakula District. Due to the weak financial management behavior of MSME actors in Tejakula District, for that reason, is financial management behavior influenced by financial knowledge, financial attitudes, and education levels. The novelty of this study is the use of the education level variable which has rarely been studied for its effect on financial management behavior, especially for MSME actors in Tejakula District. This study uses a quantitative research method with data collection in the form of questionnaires distributed to respondents. The population used in this study were all MSME actors in Tejakula District in 2024 totaling 7,663. The sample determination was carried out using the purposive sampling technique with the help of the Slovin formula, so that the number of samples used in this study was 99 respondents. The data used in this study is primary data which is then analyzed using descriptive analysis, data quality testing, classical assumption testing, and hypothesis testing using SPSS tools. Based on the results of this study, it was found that the financial knowledge variable influences the financial management behavior of MSME actors in Tejakula District. Furthermore, the financial attitude variable influences the financial management behavior of MSME actors in Tejakula District. And finally, the education level variable influences the financial management behavior of MSME actors in Tejakula District. This shows that the greater the financial knowledge, financial attitude, and education level, the more it will improve the financial management behavior of MSME actors in Tejakula District. The practical implications of this study state that the financial management behavior of MSME actors is influenced by these three factors, where the better the financial knowledge, financial attitude, and education level of MSME actors, the better the financial management behavior of MSME actors in Tejakula District.